Effects of methanol in blood pressure and heart rate in the rat - Kausar Jahan; D Mahmood; M Fahim (Wolters Kluwer Medknow Publications, 2015)
Introduction: Methanol ingestion is an uncommon form of poisoning that can cause severe metabolic disturbances, blindness, permanent neurologic dysfunction and death. While methanol itself may be harmless, it converts, in vivo, to highly toxic formic acid. Methanol intoxication clinically manifests as ocular toxicity. The present study investigated the cardiovascular effects of methanol. Materials and Methods: On the day of the experiment, Wistar rats were anesthetized with urethane. The femoral artery on one side was exposed, and a polyethylene catheter was inserted into the artery for recording arterial blood pressure (ABP). The catheter was attached to a pressure transducer (Statham - P23D). Systolic blood pressure (BP), mean ABP, and heart rate were recorded on a power-lab data acquisition system with a computerized analysis program. Rats were administered with different dilutions (9.5%, 19.0%, 28.5%, 38.0%, 47.5%, 57.0%, 66.5%, 76%) of methanol (95% v/v, i.v.). Results: Of all dilutions of methanol, 66.5% dilution showed maximum decrease of diastolic BP from 124.64 ± 5.39 to 62.30 ± 11.90 mmHg; 76.0% dilution showed maximum decrease of systolic BP from 165.70 ± 5.57 to 112.11 ± 12.0 mmHg, and mean ABP from 160.61 ± 12.45 to 86.14 ± 4.11 mmHg. The heart rate increased (from 250 beats/s to near about 275 beats/s) following administration of methanol dilution from 19.0% till 76.0%. Conclusion: The present study is consistent with previous studies suggesting that methanol ingestion leads to severe hypotension as observed from decrease in diastolic BP, systolic BP, and mean ABP. However, severe increase of heart rate suggests activation of a compensatory mechanism to offset hypotension that eventually leads to death in methanol poisoning. Hence, this study emphasizes the need to monitor all the hemodynamic parameters in accidental methanol poisoning.